Phase I and Pharmacokinetic Study of 10-Propargyl-10-Deazaaminopterin, a New Antifolate - Krug, L. (Institutional Knowledge at Singapore Management University, 2000)
The 10-deazaaminopterins are a new class of rationally designed antifolates demonstrating greater antitumor effects than methotrexate in murine tumor models and human tumor xenografts. Their design was aimed at improving membrane transport and polyglutamylation in tumor cells, resulting in increased intracellular accumulation and enhanced cytotoxicity. Compared with other 4-aminofolate analogues, 10-propargyl-10-deazaaminopterin (PDX) is the most efficient permeant for the RFC-1-mediated internalization and substrate for folylpolyglutamate synthetase. PDX demonstrates greater in vitro and in vivo antitumor efficacy than methotrexate or edatrexate. We undertook a Phase I study with PDX to identify the potential toxicities and define an optimal dose and schedule. Thirty-three patients were enrolled, all of whom had non-small cell lung cancer (NSCLC) and were treated previously with a median of two prior chemotherapy regimens. Initially, PDX was administered weekly for 3 weeks in a 4-week cycle. Mucositis requiring dose reduction and/or delay in the first cycle occurred in four of six patients treated at the initial dose level (30 mg/m2), making this the maximal tolerated dose for PDX given on this schedule. The treatment schedule was then modified to every 2 weeks. Twenty-seven patients were treated twice weekly with a total of 102 four-week cycles (median, 2 cycles/patient). Mucositis was the dose-limiting toxicity, with grade 3 and 4 mucositis occurring in the first two patients treated at the 170 mg/m2 dose level. Other toxicities were mild and reversible. No neutropenia was observed. The recommended Phase II dose is 150 mg/m2 biweekly. At that dose level, the mean area under the curve was 20.6 micromolmiddle doth, and the mean terminal half-life was 8 h. Two patients with stage IV NSCLC had major objective responses, and five patients had stable disease for 7 (two patients), 9 (one patient), 10 (one patient), and 13 months (one patient). PDX is a new antifolate with manageable toxicity and evidence of antitumor activity in NSCLC. A Phase II trial in NSCLC and a Phase I trial with paclitaxel are under way. These studies will also quantitate the expression of genes controlling internalization (RFC-1) and polyglutamylation of PDX in tumor cells as correlates of response.